Overlap of disease susceptibility loci for rheumatoid arthritis and juvenile idiopathic arthritis. Issue 6 (11th August 2009) - Hinks, Anne; Eyre, Steve; Ke, Xiayi; Barton, Anne; Martin, Paul; Flynn, Edward; Packham, Jon; Worthington, Jane; Thomson, Wendy
Abstract : Background: Genome-wide association studies (GWAS) have been extremely successful in the search for susceptibility risk factors for complex genetic autoimmune diseases. As more studies are published, evidence is emerging of considerable overlap of loci between these diseases. In juvenile idiopathic arthritis (JIA), another complex genetic autoimmune disease, the strategy of using information from autoimmune disease GWAS or candidate gene studies to help in the search for novel JIA susceptibility loci has been successful, with confirmed association with two genes, PTPN22 and IL2RA. Rheumatoid arthritis (RA) is an autoimmune disease that shares similar clinical and pathological features with JIA and, therefore, recently identified confirmed RA susceptibility loci are also excellent JIA candidate loci. Objective: To determine the overlap of disease susceptibility loci for RA and JIA. Methods: Fifteen single nucleotide polymorphisms (SNPs) at nine RA-associated loci were genotyped in Caucasian patients with JIA (n=1054) and controls (n=3531) and tested for association with JIA. Allele and genotype frequencies were compared between cases and controls using the genetic analysis software, PLINK. Results: Two JIA susceptibility loci were identified, one of which was a novel JIA association ( STAT4 ) and the second confirmed previously published associations of the TRAF1 / C5 locus with JIA. Weak evidence of association of JIA with three additional loci (Chr6q23, KIF5A and PRKCQ ) was also obtained, which warrants further investigation. Conclusion: All these loci are good candidates in view of the known pathogenesis of JIA, as genes within these regions ( TRAF1, STAT4, TNFAIP3, PRKCQ ) are known to be involved in T-cell receptor signalling or activation pathways.